Comparative Morphometric Rhizophora Apiculata Leaf And Fruit In Two Areas With Anthropogenic Activities Different In Pesisir Dumai Barat Kota Dumai ProvinsiRiau - David Raymond Sianturi; Efriyeldi Efriyeldi; Aras Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTMorphometrics is a field that deals with variations and changes in the form (size and shape) of an organism or object. Anthropogenic is a human activity not only limited to the use or utilization of coastal resources, but also can be restorative and protective, thus causing complex disruption. The purpose of this study was to determine the morphometric differences of the leaves and fruits of R. apiculata mangroves in two regions with different anthropogenic activities in the mangrove ecosystem of Dumai City. This research was carried out in May 2019. From the results of the study it was found that in areas polluted by anthropogenic activity the average morphometrics of fruit (length and width) and leaves (length, width and length of the stems) Rhizophora apiculata were lower than those in the area not polluted by anthropogenic activity. At station I the oil content ranged from 1162.11 to 1934.2 ppm classified as polluted and at station II ranged from 672.81 – 1082.30 ppm classified as not polluted. The content of organic matter at station I ranged from 11.03 to 13.73%, which was classified as low, while at station II it ranged from 19.95 to 23.77% which was classified as moderate. Keywords:Dumai, Anthropogenic, Mangrove, Morphometric